Extremal rank-one convex integrands and a conjecture of Šverák - Guerra, A (Springer Verlag, 2019)
We show that, in order to decide whether a given probability measure is laminate, it is enough to verify Jensen’s inequality in the class of extremal non-negative rank-one convex integrands. We also identify a subclass of these extremal integrands, consisting of truncated minors, thus proving a conjecture made by Šverák (Arch Ration Mech Anal 119(4):293–300, 1992).